Characterization of a thermosensitive Escherichia coli aspartyl-tRNA synthetase mutant. - Martin, F (1997)
The Escherichia coli tls-1 strain carrying a mutated aspS gene (coding for aspartyl-tRNA synthetase), which causes a temperature-sensitive growth phenotype, was cloned by PCR, sequenced, and shown to contain a single mutation resulting in substitution by serine of the highly conserved proline 555, which is located in motif 3. When an aspS fragment spanning the codon for proline 555 was transformed into the tls-1 strain, it was shown to restore the wild-type phenotype via homologous recombination with the chromosomal tls-1 allele. The mutated AspRS purified from an overproducing strain displayed marked temperature sensitivity, with half-life values of 22 and 68 min (at 42 degrees C), respectively, for tRNA aminoacylation and ATP/PPi exchange activities. Km values for aspartic acid, ATP, and tRNA(Asp) did not significantly differ from those of the native enzyme; thus, mutation Pro555Ser lowers the stability of the functional configuration of both the acylation and the amino acid activation sites but has no significant effect on substrate binding. This decrease in stability appears to be related to a conformational change, as shown by gel filtration analysis. Structural data strongly suggest that the Pro555Ser mutation lowers the stability of the Lys556 and Thr557 positions, since these two residues, as shown by the crystallographic structure of the enzyme, are involved in the active site and in contacts with the tRNA acceptor arm, respectively.